The Last Oil Shock : A Survival Guide to the Imminent Extinction of Petroleum Man - Strahan, David (London John Murray, 2008)
"The terminal decline of oil production will spark a crisis more dangerous than terrorism and just as urgent as climate change. World leaders know it, so why aren't they telling? David Strahan explains how we have reached this critical state and how you can protect yourself and your family from the ravagees of the last oil shock."
Include Notes and Index
Keywords: Petroleum reserves--Forecasting -- Petroleum conservation -- Petroleum products--Prices